PERSEPSI GURU PAI DI MAN KOTA MALANG TENTANG PENDIDIKAN ANTI KORUPSI (Usaha Merekonstruksi Kurikulum Pendidikan Anti Korupsi di Madrasah Aliyah) - Rahmawati Baharuddin (lp2m-uin malang, 2010)
Corruption is one of big problems of Indonesia, every side of this nation has been suffered by corruption. From the lowest upto top level of government. Corruption eradication can not be done quickly but step by step simultaniously. There are many ways and methods that can be applied, one of them is by making anti-corruption curriculum for our students.anti-corruption education is one of moral teachings that has relation with religion study. So that, the researcher takes teachers of subject of Islamic religion as subjects of this study, especially for Islamic Jurisprudence (Fiqh), al-Qur’an-Hadith, and Aqidah Akhlaq in three state islamic senior high schools in Malang City. The focus of this research is to describe how are their perceptions toward anti-corruption curriculum for our student. By using qualitative approach with emic perspective, the researcher finds that there four kinds of perceptions toward anti-corruption curriculum. That are; it should be as one additional subject; it can be supplement for existed subjects; it should be done outside formal education; and it may give in university level. However, the teachers agree that the values of anti corruption curriculum will be put on education institutions.